2020
DOI: 10.5327/z2176-947820200705
|View full text |Cite
|
Sign up to set email alerts
|

Serviços ecossistêmicos no planejamento integrado do território metropolitano: oferta, demanda e pressões sobre a provisão de água na região metropolitana de Curitiba

Abstract: A sustentabilidade dos assentamentos humanos, principalmente áreas urbanas, e dos ecossistemas como um todo envolve a adoção de estratégias territoriais integradoras, que levem em conta os aspectos ambientais, econômicos, sociais e culturais. O enfoque dos serviços ecossistêmicos pode ser aliado no fortalecimento da visão integrada do território metropolitano e da água como elemento-chave integrador. Nesse contexto, este estudo teve como objetivo a proposição de um conjunto de indicadores de avaliação de capit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The distance of parks from their users' locations must be considered in the planning and supply of these areas; otherwise, this could result in a demand pressure on ecosystem services, especially those in more urbanized locations. Carbone et al (2020) suggested urbanization as a factor directly associated with an increased demand for ecosystem services. Regarding the minimum distance of access to urban green areas, there are recommendations that at least 2 ha would be available within 300 m of all inhabitants (WHO, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The distance of parks from their users' locations must be considered in the planning and supply of these areas; otherwise, this could result in a demand pressure on ecosystem services, especially those in more urbanized locations. Carbone et al (2020) suggested urbanization as a factor directly associated with an increased demand for ecosystem services. Regarding the minimum distance of access to urban green areas, there are recommendations that at least 2 ha would be available within 300 m of all inhabitants (WHO, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, rapid urbanization that occurs in large Brazilian metropolises has been generating various environmental and social problems and has resulted in severe ecosystem services degradation (Carbone et al, 2020), as well as threats to conservation areas. Examples of negative impacts related to increasing population density and demands of urban environments that emerge in mega cities are floods, insufficient water availability, the urban heat island effect, poor air quality, and noise pollution, all of which are expected to be further exacerbated by the vulnerability of each region to climate change impacts, affecting human health and the well-being of population and ecosystems (Lourdes et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This process of metropolization generates a concentration of economic activities and essential services (Polèse and Shearmur, 2004), producing new urban morphologies (Moura, 2012), with environmental and social problems, poverty, social and territorial segregation; violence; crime; deterioration of the environment, and quality of life (Fernandes and Vieira, 2021). The metropolises are, therefore, a significant challenge to management and metropolitan governance that involves different social actors, scales, territorial and functional spaces, and shared planning actions that can intrinsically reconcile socio-economic and environmental development demands (Frey, 2012;Carbone at al., 2020).…”
Section: Introductionmentioning
confidence: 99%